Cavell, Companionship, and Christian Theology. By Peter Dula - McGhee, Michael (The journal of theological studies, 2013)
This book offers a refreshing, sensitive, intelligent, and above all creative appraisal of the work of the great American philosopher Stanley Cavell as it bears upon theology and the philosophy of religion—and in doing so attempts ambitiously enough to take the pulse of recent American history and culture.